The Importance of Good Governance in the Government Organization - R. Luki Karunia; Darmawansyah Darmawansyah; Kurnia Sari Dewi; Johan Hendri Prasetyo (HighTech and Innovation Journal, 2023)
The intention of this research was to evaluate the influence of the implementation of good governance on the performance of one of the government organizations. The method used was a quantitative-descriptive with causality approach, which was then analyzed by PLS-SEM. The amount of the research sample was 303 of state civil apparatus at the Land Transportation Management Center throughout 38 provinces in Indonesia. The research findings explained that transparency has an impact on the increasing accountability and responsibility of government organizations but has no power to boost their performance. Accountability has an influence on increasing responsibility and the performance of an organization. Responsibility is also found to be effective in rebuilding the performance of government organizations. This research brings the latest issue to the surface. By linking all indicators of good governance factors, namely transparency-accountability, transparency-responsibility, and accountability-responsibility, which is rarely done in previous research that focused on the connection between good governance-performance. In addition to that, this research was also conducted at the Land Transportation Management Center throughout 38 provinces, so the level of accuracy would be high and had a huge impact on related government organizations in Indonesia.